Exploration of Nurses Experience in Managing Emotions While Involved in Covid-19 Care: A Qualitative Study - Liza Fauzia; Fitri A. Sabil; Muzakkir Muzakkir (Jurnal Ilmiah Kesehatan (JIKA), 2022)
The coronavirus disease (Covid-19) pandemik brings pressure and challenges on health workers, especially nurses. One of the effects is psychological pressure. This study aimed to explore the experience of nurses in managing emotions while involved in Covid-19 care. This research was a qualitative study with a phenomenological approach. Data collection was carried out using interview guidelines which was then analyzed using data content analysis. Total sample 7 participants. The results showed 3 outcome themes, namely emotional status when involved in Covid-19 treatment: scared, anxiety and stress. The theme of the support system is: hospital management, colleagues, family and the theme of coping and self care style: distraction, improving spiritually and professionally at work. The conclusion of this study showed nurses are able to adapt and have good coping and self-care while involved in the treatment of Covid-19, besides that the support system from the hospital, colleagues, family is given so that it suppresses emotions while involved in the treatment of Covid-19.